Car park designers' handbook - Hill, Jim, 1931-; Rhodes, Glynn; Vollar, Steve (ICE Publishing, 2014)
This book intends to help practising engineers, designers, architects, local authorities, parking consultants and operators to create car parks which not only meet the spatial needs of motorists, but achieve economy of construction, durability of structure and effective use of the site area.